2008
DOI: 10.1266/ggs.83.153
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional properties of Viviparous1 genes in dormant wheat

Abstract: Viviparous 1 (Vp1) of maize is known to encode a transcription factor VP1 that controls seed germination. Hexaploid wheat possesses three Vp1 homoeologues (TaVp1): TaVp-A1, . In this study, we attempted to characterize the molecular properties of TaVp1 in a highly dormant wheat cultivar, Minamino-komugi (Minamino). The seeds of Minamino showed much higher sensitivity to the inhibitory effect of ABA on germination than those of non-dormant cultivars, Sanin-1 and Tozan-18. The sequence analyses of cDNAs also rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 46 publications
1
23
0
2
Order By: Relevance
“…For both cultivars, in non-sprouting grains we found a higher expression level of the VP1 gene in comparison to sprouting grain but only in Piko this difference was significant. A similar correlation was found by Utsugi et al (2008) for isolated wheat embryos of dormant and dormancy-broken grains. In our research, the VP1 transcript was more abundant in non-sprouting grains of Piko (PHS-susceptible) than in non-sprouting grains of Sława (PHS-tolerant).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…For both cultivars, in non-sprouting grains we found a higher expression level of the VP1 gene in comparison to sprouting grain but only in Piko this difference was significant. A similar correlation was found by Utsugi et al (2008) for isolated wheat embryos of dormant and dormancy-broken grains. In our research, the VP1 transcript was more abundant in non-sprouting grains of Piko (PHS-susceptible) than in non-sprouting grains of Sława (PHS-tolerant).…”
Section: Discussionsupporting
confidence: 84%
“…Several studies described the correlation between susceptibility to PHS and response of wheat grains to ABA treatment. Cultivars that are resistant / tolerant to PHS are more sensitive to ABA than susceptible cultivars (Walker-Simmons, 1987;Corbineau et al, 2000;Utsugi et al, 2008). In our studies, the grains tested after a 5-week storage showed weaker dormancy when compared to grains examined directly after harvest (45 DAP).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…PHS resistance has been shown to be associated not with higher ABA levels in dry seeds, but with higher ABA sensitivity during embryo maturation and during seed germination in some cultivars (Walker-Simmons 1987;Morris et al 1989). Wheat varieties showing higher seed dormancy are much more sensitive to the germination inhibitory action of exogenously applied ABA than non-dormant varieties (Walker-Simmons 1987; Morris et al 1989;Corbineau et al 2000;Utsugi et al 2008). The seeds of one Japanese wheat cultivar Minamino showed much higher sensitivity to the inhibitory effect of ABA on germination than those of nondormant cultivars, Sanin-1 and Tozan-18, and the expression of Vp-1 gene played an important role in controlling dormancy in Minamino (Utsugi et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Wheat varieties showing higher seed dormancy are much more sensitive to the germination inhibitory action of exogenously applied ABA than non-dormant varieties (Walker-Simmons 1987; Morris et al 1989;Corbineau et al 2000;Utsugi et al 2008). The seeds of one Japanese wheat cultivar Minamino showed much higher sensitivity to the inhibitory effect of ABA on germination than those of nondormant cultivars, Sanin-1 and Tozan-18, and the expression of Vp-1 gene played an important role in controlling dormancy in Minamino (Utsugi et al 2008). In this study, we determined the GI and ABA sensitivity of eight accessions, each representing one Vp-1A haplotype.…”
Section: Discussionmentioning
confidence: 99%